Effects of the heavy metals Cu2+, Ni2+, Pb2+ and Zn2+ on some physiological parameters of the lichen Usnea amblyoclada to air pollutants - Carreras, Hebe Alejandra (2007)
The effect of Cu2+, Ni2+, Pb2+, and Zn2+ on some physiological parameters of the lichen Usnea amblyoclada and the selective uptake of Cu2+ and Pb2+ was assessed. Fresh thalli were soaked in single or mixed metallic solutions. The concentration of chlorophylls and malondialdehyde; the dry weight/fresh weight ratio as well as the water content and the concentration of Cu, Ni, Pb, and Zn were measured in the treated and control thalli. The exposure to Cu, Ni, and Pb solutions caused several changes on the parameters measured; no differences were found with Zn. A stronger ability for binding Pb2+ was also observed. The results suggest that Cu2+ was the most harmful cation followed by Pb and Ni. Consequently, the damage observed in U. amblyoclada thalli when it is used as a biomonitor in polluted areas is possibly due to the presence of these heavy metals, masking the effect of other gaseous pollutants.